2023
DOI: 10.1002/eji.202250123
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing pyroptosis via hyperactivation shapes superior immune responses of human type 2 dendritic cells compared to type 3 dendritic cells

Abstract: Exploiting inflammasome activation in dendritic cells (DCs) is a promising approach to fight cancer and to augment adjuvant‐induced immune responses. As inflammasome formation is typically accompanied by pyroptosis, hyperactivation—defined as inflammasome activation in the absence of pyroptosis—represents a mechanism of circumventing cell death of DCs while simultaneously benefitting from inflammasome signaling. We previously demonstrated a unique specialization for inflammasome responses and hyperactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Additionally, a recent investigation proposed another distinction between cDC2 subpopulations. This heterogeneity is characterized by the presence of two distinct subpopulations in human, now known as DC2 and DC3 ( 50 ). Single-cell RNA-seq analysis has revealed that both subpopulations exhibit similar gene expression patterns related to inflammasome signaling under steady-state conditions ( 51 ).…”
Section: Target Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a recent investigation proposed another distinction between cDC2 subpopulations. This heterogeneity is characterized by the presence of two distinct subpopulations in human, now known as DC2 and DC3 ( 50 ). Single-cell RNA-seq analysis has revealed that both subpopulations exhibit similar gene expression patterns related to inflammasome signaling under steady-state conditions ( 51 ).…”
Section: Target Cellsmentioning
confidence: 99%
“…The T cell responses induced by DC2 are predominantly skewed toward a Th1/Th17 phenotype. Thus, it appears that DC2 subpopulation has the ability to enter a state of hyperactivation, resulting in enhanced T cell stimulatory capabilities ( 50 ). Last, this distinction between DC2 and DC3 in human has also been conversely observed in mice ( 53 ).…”
Section: Target Cellsmentioning
confidence: 99%
See 1 more Smart Citation